2012
DOI: 10.1002/app.37811
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the elongation at break of polyhydroxybutyrate biopolymer: Effect of cellulose nanowhiskers on mechanical and thermal properties

Abstract: Bionanocomposites based on polyhydroxybutyrate (PHB) and cellulose nanowhiskers (CNWs) were prepared by dispersing CNWs in poly(ethylene glycol) (PEG) plasticizer subsequently incorporating the CNWs/PEG suspensions in the matrix. The thermal properties of the nanocomposites indicate an enlargement in the processing window in comparison to the neat PHB. The nanocomposites showed a remarkable increase in the strain level (50 times related to the neat PHB), without a significant loss of the tensile strength with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…Patrício et al incorporated cellulose nanowhiskers (CNWs) into PHB by dispersion in plasticizing agent polyethylene glycol (PEG) (110). For concentrations of CNWs up to 0.45 wt.…”
Section: Polyhydroxybutyrate-based Compositesmentioning
confidence: 99%
“…Patrício et al incorporated cellulose nanowhiskers (CNWs) into PHB by dispersion in plasticizing agent polyethylene glycol (PEG) (110). For concentrations of CNWs up to 0.45 wt.…”
Section: Polyhydroxybutyrate-based Compositesmentioning
confidence: 99%
“…Moreover in these studies, the presence of PEG 1500 melting peak was observed in all the samples based on PHB with PEG 1500 suggesting that PEG 1500 is not completely compatible with PHB, as confirmed by separation observed in the samples with ageing. In the preparation of nanocomposites of PHB with cellulose nanowhiskers (CNW) prepared through the previous dispersion of CNWs in polyethylene glycol (PEG) and subsequent incorporation of the PEG/nano whiskers dispersions into the biopolymer, it was observed that for CNW concentrations up to 0.45 wt%, the CNWs were covered by PEG, and the interaction between the PHB and the CNWs occurred preferentially with PEG ( [43]). The adhesion of PEG to the natural fibres can explain the lubricating effect of PEG in the preparation of composites with PHB and natural fibres.…”
Section: Blending Of Phb With Other Polymers Ormentioning
confidence: 99%
“…Unfortunately materials of different HV content are hardly available in kg scale on the market. Plasticising as an alternative strategy can be found in literature but these studies often do not compare different plasticisers [13][14][15] or investigate PHBV in combination with another biopolymer [16,17] or with another additive [18,19]. The interesting approach of this study is the comparison of different types and molecular weights of plasticisers on the PHBV.…”
Section: Introductionmentioning
confidence: 99%